Evaluasi Sistem Kewaspadaan Dini dan Respon Penyakit (SKDR) Provinsi Daerah Istimewa Yogyakarta tahun 2022 - Astari Marullyta; R Rohananingsih (Multidisciplinary Journal, 2022)
Indonesia is a country with high population movements as well as urbanization, this causes new emerging and re-emerging diseases such as malaria, diarrhea, cholera, diphtheria, anthrax, rabies, measles, pertussis, and Covid 19. Which can cause infectious diseases and outbreaks. The Early Warning and Response System (EWARS) is a web-based syndrome surveillance system used to detect any abnormal phenomenon that will trigger prompt public health intervention. This study aims to describe performance of the reporting system and management of EWARS implementation in the Province of Yogyakarta in 2022. This research was descriptive qualitative research by using evaluating approach. Qualitative descriptive research design using an evaluation approach. The informant selection technique was carried out using purposive sampling technique through in-depth interviews, observation and document review related to the research topic. The data analysis was content analysis. Validity test used was sources triangulation, methods and data. The results showed that Province of Yogyakarta had a timeliness of reports was 96.32%, completeness of reports was 99.43%, and 100% alerts responded. Meanwhile most of the data on the number of diseases in the EWARS did not match the report manual reports. EWARS has been carried out well in Province of Yogyakarta which can be seen from Timeliness, completeness, and alert responded, but needs to be improved in terms of data validation on the number of disease reports.